2016
DOI: 10.1016/j.chemphys.2016.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Product channels in the 193-nm photodissociation of HCNO (fulminic acid)

Abstract: IR diode laser spectroscopy was used to detect the products of HCNO (fulminic acid) photolysis at 193 nm. Six product channels are energetically possible at this photolysis wavelength: O + HCN, H + NCO/CNO, CN + OH, CO + NH, NO + CH and HNCO. In some experiments, isotopically labeled 15 N 18 O, C 2 D 6 or C 6 H 12 reagents were included into the photolysis mixture in order to suppress and/or redirect possible secondary reactions. HCN, OC 18 O, 15 N 15 NO, CO, DCN and HNCO molecules were detected upon laser pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Later, Grußdorf et al [16] reported that the dominant channel is HCNO + H, accounting for about 84%. The physicochemical properties of HCNO, and its reactions with various species present in hydrocarbon combustion such as H-and O-atoms, HO x radicals, and other reactive species have been investigated [3,[17][18][19][20][21][22][23][24][25][26][27][28][29]. Theoretical studies showed that there are two main mechanisms for the reactions of HCNO, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Grußdorf et al [16] reported that the dominant channel is HCNO + H, accounting for about 84%. The physicochemical properties of HCNO, and its reactions with various species present in hydrocarbon combustion such as H-and O-atoms, HO x radicals, and other reactive species have been investigated [3,[17][18][19][20][21][22][23][24][25][26][27][28][29]. Theoretical studies showed that there are two main mechanisms for the reactions of HCNO, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…19 Particularly relevant for the present work are studies by Mondal et al 20 on the appearance of Jahn-Teller and Renner-Teller interactions in HCNO + as well as the work by Luna et al who published the global potential energy surface of the [H,C,N,O] + system using density functional theory. 21 Experimentally the microwave [22][23][24] and IR-spectra [24][25][26][27][28][29][30][31][32] have been reported, the photodissociation has been investigated at 248 nm 33 and 193 nm 34 and the kinetics of the HCNO + OH reaction has been studied 35 . In the soft X-ray regime, we recently reported normal and resonant Auger spectra of HCNO at all three K-edges.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Additionally, Feng et al studied the reaction kinetics with OH 14 and the photodissociation of HCNO at 248 nm and 193 nm. 15,16 In contrast, no studies in the X-ray regime have been reported yet. Because HCNO consists of only 4 atoms and 22 electrons it has also been attractive for theoretical chemists early on.…”
Section: Introductionmentioning
confidence: 99%